If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 12 + x + -1 + 2 Reorder the terms: -3 + 5x = 12 + x + -1 + 2 Reorder the terms: -3 + 5x = 12 + -1 + 2 + x Combine like terms: 12 + -1 = 11 -3 + 5x = 11 + 2 + x Combine like terms: 11 + 2 = 13 -3 + 5x = 13 + x Solving -3 + 5x = 13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 5x + -1x = 13 + x + -1x Combine like terms: 5x + -1x = 4x -3 + 4x = 13 + x + -1x Combine like terms: x + -1x = 0 -3 + 4x = 13 + 0 -3 + 4x = 13 Add '3' to each side of the equation. -3 + 3 + 4x = 13 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 13 + 3 4x = 13 + 3 Combine like terms: 13 + 3 = 16 4x = 16 Divide each side by '4'. x = 4 Simplifying x = 4
| 40+2*5= | | k^4-100k=0 | | 3/2x-1/3x | | 0=-16t^2+4.5t | | 16c^2-70c+49=0 | | 1/2=d/4 | | 8-x=3x+8 | | 3x+1x=36 | | y/50=-21 | | 2x^4-13x^2+17=0 | | p/2.3=4 | | a+b=19 | | x/5.3=0.7 | | 80=-8k | | -5=1.5(6x-2)+7x | | 4(4x+2)=21x+6-5x+2 | | x/2=4=13 | | b/3=8.2 | | 15y+3=-36-18y | | 12-(2x+3)=13 | | b/3=8. | | -12=a/-3 | | 16=x-13 | | (3x+6)+8=-13 | | x/-6=13 | | t/28=9 | | 33=6r+3 | | (2-w)(4w-7)=0 | | 5x-8y=-18 | | cos^(2)x-7/2cos(x)-2 | | ((z^(4/3))(y^(-3)))^(1/4) | | 5s+4t-2s-(-3t)= |